Trigonometria por apps - Mastronicola, Natália Ojeda (Universidade Federal de São Carlos, 2014)
In this work the author intends to show an experience of implementation of alternative activities to traditional teaching of trigonometry in 9th year of Fundamental School (Brazilian curriculum). The theme choice came from the author's finding of difficulties presented by pupils in face of a great amount of formulas without meaning for them. The goal of these activities was to stimulate the students to make them construct their own knowledge, culminating in a meaningful learning. It was intended to formulate activities with the use of smartphones and tablets. The technological advance of cell phones has provided a range of different tools that fit in someone's palm and can be accessed immediately. Some of these tools provide the use of tablets and smartphones in the educational context, aiding student's learning in an innovative form, making it more pleasurable. All activities followed the guidelines of didactical engineering as research methodology. The activities were applied in a school were the author is a teacher.
Keywords: Trigonometria; Matemática - ensino; Engenharia didática; GeoGebra (Software de computador); Smartphones; Tablet (Computador); Trigonometry; Mathematics teaching; Didactical engineering; Apps; CIENCIAS EXATAS E DA TERRA